Free Will Skepticism, Quarantine, and Corrections (Diametros, 2024)
This article compares the quarantine model of criminal justice advocated by Derk Pereboom and Gregg Caruso with the corrections model of criminal justice advocated by Michael Corrado.  Both of these theories are grounded on the presumption that persons lack desert-grounding free will.  It is argued that on this presumption there is no reason to believe that Michael Corrado’s corrections model is any better than the quarantine model.
Keywords: free will skepticism; punishment; criminal quarantine; criminal corrections; Derk Pereboom; Gregg Caruso; Michael Corrado